SEDIMENTOLOGICAL ANALYSIS OF DEEP WATER, UPSLOPEMIGRATING CROSS-BEDDED DEPOSITS IN A DISTALLY STEEPENED CARBONATE RAMP (MENORCA, BALEARIC ISLANDS, SPAIN) - ANDREETTA, Rachele (Università degli studi di Ferrara, 2009)
The upper Miocene units cropping out along the southern coast of the Island of Menorca (Balearic Islands, Spain), are mainly represented by two carbonate depositional systems: an early Tortonian distally steepened ramp (Lower Bar Unit) and an upper Tortonian – lower Messinian reef-rimmed platform prograding complex (Reef Complex). Within the distally steepened ramp, Pomar et al. (2002) distinguished four facies belts: fan-delta conglomerates passing upwards to bioturbated packstones (inner ramp), cross-bedded grainstones (middle- ramp), clinostratified rhodolithic rudstone (ramp slope) and fine-grained wackestonepackstone with planktonic foraminifera (outer ramp). The backset-bedded units analysed in this work are placed at the transition between toe-of-slope and outer ramp sediments, below the wave-base-level. They infill the axial depression of large slide/slump scars. These scars truncate the gently, 10°- 12° basinward dipping, slope-to-outer ramp clinoforms. Backset beds are cross-bedded forms that dip against the direction of flow of the depositing currents, therefore they present foresets migrating upcurrent (Gary et al., 1972). These sedimentary structures are well known and largely described on the foreset and toeset of Gilbert-type fan delta (Postma, 1984; Massari, 1984, 1996; Nemec, 1990). In carbonate depositional systems these type of bedforms are rarely found and only little described. The backset-bedded units, here analysed, are channel-like, wedge-shaped, 10-12 m thick, pinching out landward and extend laterally for tens of meters. Each unit is formed by several amalgamated set of backset beds, 40 cm to 2 m thick. These units are mainly conglomerates composed by bioclastic coarse-grained grainstone to rudstone. Large components are rhodoliths, bivalves, skeletal and ooid-rich pebbles to boulders, gastropods and corals. Matrix is of a bioclastic coarse-grained sand to fine gravel, made of fragments of bivalves, gastropods, rhodoliths, bryozoans, algae, echinoids, loose ooids and planktonic and ...